Tubular B7-1 expression parallels proteinuria levels, but not clinical outcomes in adult minimal change disease patients - Lee, Sung Woo (Sci Rep, 2017)
B7-1 is thought to play a pathogenic role in minimal-change disease (MCD). Recently, however, doubts have arisen regarding the role of B7-1 expression in MCD. Therefore, we aimed to identify the presence and clinical significance of B7-1 expression in MCD patients. The study participants included 28 adult MCD patients for whom kidney specimens were available. The intensity of B7-1 expression was assessed by two independent specialists. We analysed the association between the intensity of B7-1 expression and clinicopathological variables. No B7-1 expression in the glomeruli was observed in any of the 28 patients. Unexpectedly, however, 75.0% of the patients exhibited tubular B7-1 expression, with 35.7% demonstrating weak positive expressions and 39.3% demonstrating strong positive expressions. The level of proteinuria significantly increased as the intensity of tubular B7-1 expression increased. We also found trends of increasing blood urea nitrogen and serum creatinine levels with increased intensity of tubular B7-1 expression. However, we could not observe definite differences in long- and short-term clinical outcomes depending on the intensity of tubular B7-1 expression. In conclusion, B7-1 was expressed in renal tubular cells but not in glomeruli in adult MCD patients. The intensity of tubular B7-1 expression paralleled proteinuria levels, but not clinical outcomes.